Η ΑΘΗΝΑ ΤΗΝ ΠΕΡΙΟΔΟ ΤΩΝ ΦΡΑΓΚΩΝ (1204-1311) - ΝΤΟΥΡΟΥ-ΗΛΙΟΠΟΥΛΟΥ, ΜΑΡΙΑ (Eoa kai Esperia, 2013)
The hegemony of Athens (later called the duchy of Athens), which was awarded to Otho de la Roche by Boniface of Montferrat, thereby establishing the Burgundian dynasty that ruled over Athens, included Attica, Boeotia and — a little later — Argos and Nauplia. The prince of Achaia was the sole sovereign, and the inhabitants were subject to Frankish rule as this was formulated in the Assizes of Romania. A complex problem concerns the denial of the duchess of Athens Helen to give oath of hommage to the prince of Achaia Florent d’Hainaut. According to Angevin documents the change of the title of dominus to duca and the hegemony to duchy was done in 1280 and not in 1260, as is recorded in the Chronicle of Morea. The last representative of Frankish rule in Athens was Gautier, son of Hughes de Brienne, who was killed by the Catalans at the battle of Orchomenos in Copais in 1311. Gautier II, the titular duke of Athens, was established in the Peloponnesian territories of Argos and Nauplia and tried unsuccessfully to regain the duchy.